Medication Appropriateness in Prehospital Care. (2nd September 2019) - Ramadanov, Nikolai; Klein, Roman; Aguilar Valdez, Abner Daniel; Behringer, Wilhelm
Abstract : Background . The aim of the present study was to determine the medication appropriateness (MA) in prehospital emergency physician deployments according to the hospital discharge diagnosis and to investigate the factors influencing the MA. Methods . The MA was determined by a systematic comparison of the administered medication in prehospital emergency physician deployments with the discharge diagnosis in a period of 24 months at the emergency medical services in Bad Belzig. Categorial variables for the specialty, medical educational status, and approval for emergency medicine of prehospital emergency physicians were examined univariate for relations with the MA, using the χ 2 test with the significance level ofp = 0.05 . Results . The MA was present in 69% ( n = 488) cases. The MA was present in 64% of cases by specialists and in 71% by resident physicians (p = 0.04 ). The specialty and the approval for emergency medicine of the prehospital emergency physician did not show significant results. MA was present in 46% ( n = 100) of cases with incorrect diagnoses, and it was present in 79% ( n = 388) of cases with correct diagnoses by the prehospital emergency physician (p = 0.01 ). In cases of missing MA, 224 drugs and 23 different drugs were administered by the prehospital emergency physician. Conclusions . The MA in prehospital emergency physician deployments shows a necessity for improvement with 31% medication errors. Incorrect diagnoses by the prehospital emergency physician seem to lead to medication errors in prehospital emergency physician deployments. The necessary standards and guidelines for administration of drugs should be taken into account in educational courses. The wide-ranging emergency medical training and the rapid accumulation of operational experience seem to play a crucial role for correct administration of medication in the prehospital emergency physician deployments.